TI_GERICHTE 52.2011.330 vom 22. Juni 2012 , Licenza edilizia per una termopompa. Principio di prevenzione delle emissioni - TI Tribunale d'appello (2012)
Licenza edilizia per una termopompa. Principio di prevenzione delle emissioni